EVALUATION OF GASTRIC ANTISECRETORY ANTIULCER ACTIVITY OF JAMBIRA (CITRUS LIMON LINN.): AN EXPERIMENTAL STUDY - Kumari Rita, (International Journal of Ayurveda and Pharma Research, 2019)
Acid peptic disorders, especially hyperacidity is not uncommon in the current era because of altered life style of human being. In India prevalence of H. Pyloric infection in young age is 83.8%. Peptic ulcer occurs at young age with highest incidence between 20-40 years, men are affected more than women. If these Acid peptic disorders are not treated in time, it may lead to peptic ulcer, haematemasis, malena and perforation of duodenal ulcer which are common now a day with 50% mortality.Generally it is accepted that gastric ulcers result from an imbalance between aggressive factors and the maintenance of the mucosal integrity through endogenous defense mechanisms. Use of synthetic antiulcer drugs may damage to the cell membrane of mucosal, parietal and endothelial cells. To avoid such hazards, it is essential to find out some antiulcer agents from Ayurvedic treasure of therapeutics.Ancient sages have explained many herbal preparations which are beneficial in pain in abdomen (Shoola) and/or hyperacidity (Amlapitta) etc. Jambira (Citrus limon Linn.), mentioned as Shoola-hara (pain relieving) drug in Ayurvedic classics, is abundantly available and cost effective drug and may satisfy the need of present day situation by acting as potent herbal antacid drug. With this perspective, the study was taken for the critical assessment of gastric anti-secretory and anti-ulcer activity of Jambira (Citrus limon Linn.) as an experimental study but the results of experimental study did not support that Jambira (Citrus limon Linn.) fruit juice is a potent antisecretory and antiulcer natural source compared to control in pylorus ligation rat model.